Association of menopausal sexual dysfunction with demographic and obstetric factors in postmenopausal women in Hamadan, Iran - Alavipour, Narges; Masoumi, Seyedeh Zahra; Kazemi, Farideh; Parsa, Parisa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Sexual dysfunction is a common menopausal problem that may be affected by demographic factors. The present study aimed to determine demographic and obstetric factors affecting sexual dysfunction in menopause. Methods: The present cross-sectional descriptive-analytical study was conducted on 315 postmenopausal women in Hamadan. The research instruments included demographic questionnaire, and female sexual function index (FSFI). Univariate and multivariate linear regressions were used to investigate the association of different factors and sexual function at a significance level of less than 0.05. Results: The participants' mean age was 54.15±4.24 years. Their mean sexual function score was 18.92±4.25 indicating poor sexual function. The multivariate analysis indicated that increasing the number of spouse marriage, sexual function score decreased by 2.45 (p=0.006). Furthermore, the sexual function score in those, who were not satisfied with their marriage, was 5.58 points lower than those who were satisfied with their marriage status (p <0.001). Conclusions: Given the relationship between number of spouse marriage and marital satisfaction with sexual function in postmenopausal women, it is necessary to design and implement training sessions for them.